Histology, glycosaminoglycan level and cartilage stiffness in monoiodoacetate-induced osteoarthritis: comparative analysis with anterior cruciate ligament transection in rat model and human osteoarthritis - Naveen, S.V.; Ahmad, R.E.; Hui, W.J.; Suhaeb, A.M.; Murali, M.R.; Shanmugam, R.; Kamarul, Tunku (2014)
Monosodium -iodoacetate (MIA)-induced animal model of osteoarthritis (OA) is under-utilised despite having many inherent advantages. At present, there is lack of studies that directly compare the degenerative changes induced by MIA with the surgical osteoarthritis induction method and human osteoarthritis, which would further verify a greater use of this model. Therefore, we compared the histological, biochemical and biomechanical characteristics in rat model using MIA against the anterior cruciate ligament transection (ACLT) and human cartilage with clinically established osteoarthritis. The right knees of Sprague-Dawley rats were subjected to either MIA or ACLT (n=18 in each group). Six rats were used as controls. Human cartilage samples were collected and compared from patients clinically diagnosed with (n=7) and without osteoarthritis (n=3). Histological, biochemical (Glycosaminoglycans/total protein) and biomechanical (cartilage stiffness) evaluations were performed at the end of the 1st and 2nd week after OA induction. For human samples, evaluations were performed at the time of sampling. Histopathological changes in the MIA group were comparable to that observed in the ACLT group and human OA. The Mankin scores of the 3 groups were comparable (MIA: 11.5 +/- 1.0; ACLT: 10.1 +/- 1.1; human OA: 13.2 +/- 0.8). Comparable reduction in Glycosaminoglycan/total protein content in the intervention groups were observed (MIA: 7 +/- 0.6; ACLT: 6.6 +/- 0.5; human OA: 3.1 +/- 0.7). Cartilage stiffness score were 24.2 +/- 15.3 Mpa for MIA, 25.3 +/- 4.8 for ACLT and 0.5 +/- 0.0 Mpa for human OA. The MIA model produces comparable degenerative changes to ACLT and human OA with the advantage of being rapid, minimally invasive and reproducible. Therefore, wider utilisation of MIA as animal translational OA model should perhaps be advocated.